165k views
1 vote
Make x the subject of h = 4(x + 3y) + 2

2 Answers

5 votes

Answer:

x=\frac{1}{4}(h-12y-2)x=4

Step-by-step explanation:x=\frac{1}{4}(h-12y-2)x=

4

1

(h−12y−2)

Explanation:

We are given the equation h=4(x+3y)+2h=4(x+3y)+2 .

Simplifying for x, we get,

h=4(x+3y)+2h=4(x+3y)+2

i.e. h=4x+12y+2h=4x+12y+2

i.e. 4x=h-12y-24x=h−12y−2

i.e. x=\frac{1}{4}(h-12y-2)x=

4

1

(h−12y−2)

Thus, the equation for x is x=\frac{1}{4}(h-12y-2)x=

4

1

User Tooschee
by
5.1k points
2 votes
Correct answer down below
Make x the subject of h = 4(x + 3y) + 2-example-1
User Pkoch
by
5.7k points